Participation in global value chains and M&A flows - Ciani, Andrea,Gregori, Wildmer Daniel (European Commission, 2022)
This study investigates to which extent firms operating in sectors more integrated into Global Value Chains (GVC) are more likely to be involved in cross-border Mergers and Acquisitions (M&A) flows. We focus on firms acquired in the EU27 during the period 2008-2020 employing a gravity model. Results show that cross-border investments are indeed associated with sectoral GVC participation, in particular the dependence on intermediate products supplied by other countries (i.e. backward GVC participation) of the target country-sector is positively correlated with M&A flows. This evidence is confirmed when the acquired firm operates in manufacturing or high-tech sectors, and when the investor originates from OECD countries. In addition, results show that companies from countries suppling inputs to other countries are more likely to pursue a cross-border acquisition.
10419/268935
Keywords: Graue Literatur; Global Value Chains; Mergers and Acquisitions; Global Economy; Gravity model; EU firms